Antimicrobial endodontic compounds do not modulate alkylation-induced genotoxicity and oxidative stress in vitro - Ribeiro, Daniel A. [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier, 2006)
Objective: To investigate if formocresol, paramonochlorophenol, or calcium hydroxide modulate the genotoxic effects induced by the oxidatively damaging agent hydrogen peroxide (H 2O 2) or the alkylating agent methyl methanesulfonate (MMS) in vitro by using single cell gel (comet) assay. Study design: Chinese hamster ovary (CHO) cells in culture were exposed directly to formocresol, paramonochlorophenol, or calcium hydroxide (adjusted to 100 μg/mL) for 1 hour at 37°C. Subsequently the cultures were incubated with increasing concentrations (0-10 μmol/L) of MMS in phosphate-buffered solution (PBS) for 15 minutes at 37°C or of H 2O 2 at increasing concentrations (0-100 μmol/L) in distilled water for 5 minutes on ice. The negative control cells were treated with PBS for 1 hour at 37°C. The parameter from the comet assay (tail moment) was assessed by the Kruskal-Wallis nonparametric test followed by a post hoc analysis (Dunn test). Results: Clear concentration-related effects were observed for the genotoxin-exposed CHO cells. Increase of MMS-induced DNA damage was not significantly altered by the presence of the compounds tested. Similarly, no significant changes were observed when hydrogen peroxide was used with the endodontic compounds evaluated. Conclusion: Formocresol, paramonochlorophenol, and calcium hydroxide are not able to modulate alkylation-induced genotoxicity or oxidative DNA damage as depicted by the single cell gel (comet) assay. © 2006 Mosby, Inc. All rights reserved.
Keywords: 4 chlorophenol; 4-chlorophenol; alkylating agent; calcium hydroxide; chlorophenol; formocresol; hydrogen peroxide; mesylic acid methyl ester; oxidizing agent; root canal filling material; topical antiinfective agent; animal; CHO cell; comet assay; Cricetulus; DNA damage; drug effect; hamster; mutagenesis; nonparametric test; oxidative stress; Alkylating Agents; Animals; Anti-Infective Agents, Local; Calcium Hydroxide; Chlorophenols; CHO Cells; Comet Assay; Cricetinae; DNA Damage; Formocresols; Hydrogen Peroxide; Methyl Methanesulfonate; Mutagenesis; Oxidants; Oxidative Stress; Root Canal Filling Materials; Statistics, Nonparametric